Dietary Patterns Characterized by Fat Type in Association with Obesity and Type 2 Diabetes: A Longitudinal Study of UK Biobank Participants. Issue 11 (15th September 2021) - Brayner, Barbara; Kaur, Gunveen; Keske, Michelle A; Perez-Cornago, Aurora; Piernas, Carmen; Livingstone, Katherine M
ABSTRACT: Background: The fat type consumed is considered a risk factor for developing obesity and type 2 diabetes (T2D). However, these associations have not been investigated using a dietary patterns approach, which can capture combinations of foods and fat type consumed. Objectives: This study aimed to investigate associations between dietary patterns with varying proportions of SFAs, MUFAs, or PUFAs and obesity, abdominal obesity, and self-reported T2D incidence. Methods: This study included UK Biobank participants with 2 or more 24-h dietary assessments, free from the outcome of interest at recruitment, and with outcome data at follow-up ( n = 16, 523; mean follow-up: 6.3 y). Reduced rank regression was used to derive dietary patterns with SFAs, MUFAs, and PUFAs (% of energy intake) as response variables. Logistic regression, adjusted for sociodemographic and health characteristics, was used to investigate the associations between dietary patterns and obesity [BMI (kg/m 2 ) ≥30], abdominal obesity (waist circumference; men: ≥102 cm; women: ≥88 cm) and T2D incidence. Results: Two dietary patterns, DP1 and DP2, were identified: DP1 positively correlated with SFAs ( r = 0.48), MUFAs ( r = 0.67), and PUFAs ( r = 0.56), characterized by higher intake of nuts, seeds, and butter and lower intake of fruit and low-fat yogurt; DP2 positively correlated with SFAs ( r = 0.76) and negatively with PUFAs ( r = −0.64) and MUFAs ( r = −0.01), characterized by higher intake of butter and high-fat cheese and lower intake of nuts and seeds. Only DP2 was associated with higher obesity and abdominal obesity incidence (OR: 1.24; 95% CI: 1.02, 1.45; and OR: 1.19; 95% CI: 1.02, 1.38, respectively). Neither of the dietary patterns was associated with T2D incidence. Conclusions: These findings provide evidence that a dietary pattern characterized by higher SFA and lower PUFA foods is associated with obesity and abdominal obesity incidence, but not T2D.